Sustainable livelihoods of rural community through Comprehensive Village Development Programme of Bangladesh Academy for Rural Development / Shafiqul Islam. - Islam, Md. Shafiqul. (Bangladesh Academy for Rural Development, 2007)
With reference to Comilla District, Bangladesh.